A COMPREHENSIVE STUDY OF RECENT BREAKTHROUGHS IN THE MANAGEMENT OF DYNAMIC VIRAL INFECTIONS - SHARMA, ROMA; SINGH, SURABHI (International Journal of Current Pharmaceutical Research, 2023)
Infectious diseases have been known to human civilization since the dawn of humanity. Infectious disorders are caused by various microorganisms (bacteria, fungi, and viruses). Viruses are the most well-known of all microbes. Viruses are the most well-known type of microbe. They are ultramicroscopic intracellular parasites that require a host cell to survive and reproduce. Viruses have either DNA or RNA as genetic material and have been linked to various diseases in humans, animals, and plants. The war between viruses and humans is ongoing, as both will employ diverse ways to oppose each other. Antiviral treatment and improved technology development a time-consuming process. Despite advanced instruments and tight quality control systems, only a few numbers of antiviral medications or treatment technologies are approved for human use. The cause could be side effects or antiviral medication resistance. Increased understanding of viruses, their infection mechanisms, and the rapid evolution of novel antiviral methods and methodologies will accelerate the creation of novel antiviral medications. This review focuses on the worldwide picture of drug discovery for infectious diseases and contemporary improved methodologies and antiviral therapy options.